-2b+2ab=0

Simple and best practice solution for -2b+2ab=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2b+2ab=0 equation:


Simplifying
-2b + 2ab = 0

Reorder the terms:
2ab + -2b = 0

Solving
2ab + -2b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2b' to each side of the equation.
2ab + -2b + 2b = 0 + 2b

Combine like terms: -2b + 2b = 0
2ab + 0 = 0 + 2b
2ab = 0 + 2b
Remove the zero:
2ab = 2b

Divide each side by '2b'.
a = 1

Simplifying
a = 1

See similar equations:

| x+10=330 | | 10x+6=3x+15 | | 3m-1=17 | | 13+5x=5+2x | | 3t+5=6t-6 | | 88-7x=20x+19 | | 5x-13=2x+5 | | 5(x-2)=32-x | | 5(x-2)=32 | | x-10=2x+12 | | x*14-177=x*5-6 | | 175-2x=25+16 | | 1/x+1+4/3=7/x+x+4/3x+3 | | 10-2x=14-3x | | x*14+177=x*5-6 | | 10-8x=24-15x | | 13m+4n-3m+10n= | | 4x+16=12-2x | | 198-7x=38x+23 | | 229-3x=33x+17 | | 2x^2+36=17x-30 | | y^2+yt+12t^2= | | 3x-11=44 | | 9x-12=2x+2 | | 2x+13=75-5x | | -3x+10=2x+9 | | 3x+19=11x+77 | | 6x^2-1x-40=0 | | 2xy-2xy= | | 3x/5+2=4 | | 2x+4=12x-10 | | 7y+4=9-3y |

Equations solver categories